Perancangan Purwarupa Smart Car Menggunakan NodeMCU Berbasis Internet of Things - Ery Murniyasih; Luluk Suryani; Wennie Mandela; Marcelinus Petrus Saptono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Innovation in robotics and the Internet of Things is a technological trend that continues to be developed, including in transportation innovations, such as a car. What is developed in this research is the development of the application of robots and the Internet of Things (IoT) in a mini car prototype design which can be remotely controlled as well. This prototype design uses the engineering design process method which integrates all supporting devices in the form of NodeMCU with ESP8266 base as a control center that allows communication between various sensors and actuators with the internet, TT Motor Gear as an actuator and L298n as an output translator. This mini smart car is controlled using Blynk as an internet-connected controller and for remote control of car movement using a smartphone. The results of this study are the average remote control capability has a car movement delay of 0.87 seconds and 100% of cars move in all directions. The better the internet connection, the more stable the movement of the car to be driven remotely.